Forecasting the US dollar exchange rate in Iraq using the time series method (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The aim of research to forecasting of exchange rate by using time series in analysis, to find best forecasting model to exchange rate in Iraq by using monthly data for the period (2014-2016)